IMPLEMENTASI KABUPATEN LAYAK ANAK DI KABUPATEN BENGKALIS - Muhammad Arif; Agnes Arum Budiana (Prosiding Seminar Nasional Terapan Riset Inovatif (SENTRINOV), 2024)
This research aims to determine the role and implementation of a Child Friendly Regency based on Bengkalis Regency Regional Regulation Number 13 of 2019 concerning the child-friendly Bengkalis Regency Regional Action Plan in Bengkalis Regency. This research was conducted in Bengkalis Regency with the object of research being the Bengkalis Regency Women’s Empowerment and Child Protection Service. A qualitative approach with qualitative descriptive techniques was used in this research. Data analysis was obtained from interviews conducted with the Bengkalis Regency Women’s Empowerment and Child Protection Service. The results of the research show that in the implementation of Bengkalis Regency Regional Regulation Number 13 of 2019 concerning Implementation of the Bengkalis Regency Regional Action Plan which is suitable for children in Bengkalis Regency, the development of a Child Friendly Regency in Bengkalis Regency has gone quite well with the implementation of the five clusters which are indicators of a Child Friendly City, namely ( 1) civil rights and freedoms. 2) family environment and alternative care (3) basic health and well-being. (4) education, use of free time and cultural activities. (5) special protection.